2015
DOI: 10.1007/s00520-015-2744-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical rehabilitation in stem cell transplantation patients

Abstract: The purpose of this paper is to review the evidence for the role of physical rehabilitation in stem cell transplantation patients. We will also review the literature and discuss professional experiences on how rehabilitation can play a role in stem cell transplant care and survivorship. Hematopoietic stem cell transplantation (HCT) is a procedure that has evolved substantially over the years to help treat multiple conditions, particularly hematologic malignancies. HCT can be very stressful on the body and can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 71 publications
0
35
0
9
Order By: Relevance
“…Their findings demonstrated that one of the key factors in the improvement of life quality and survival of patients undergoing stem cell transplant was supportive care, especially physical medicine and rehabilitation. [31]…”
Section: Resultsmentioning
confidence: 99%
“…Their findings demonstrated that one of the key factors in the improvement of life quality and survival of patients undergoing stem cell transplant was supportive care, especially physical medicine and rehabilitation. [31]…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the scarcity of studies related to physical impairment during the acute post-transplant period, numerous studies have assessed physical impairment during the long term-post-transplant period and rehabilitation in patients that received HSCT (6,18,19). These studies generally evaluated physical function using the 6-min walk test, 50-foot walking time, repeated sit-to-stand movement, KPS, the ECOG scale, and questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since higher compliance to the home exercise program was associated with higher QOL, patients treated with HSCT should be supported to regularly participate in an exercise program. There is enough data suggesting possible bene cial effects of supervised or non-supervised exercise programs on not only QOL but also physical, psychological, cardiopulmonary functions for patients undergoing HSCT [19,20]. Telehealth technologies are now facilitated to be used by health care professionals to screen cancer patients' health care and supportive care needs [21,22].…”
Section: Discussionmentioning
confidence: 99%